“Ferguut”: the sorrows of a young hero in Netherlands’ Arthurian literature (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2022)
Compared to its Old French model, the Arthurian romance Ferguut sets different tones, especially in the second part. The desire to re-evaluate the feminine universe is, for instance, evident. In some scenes, moreover, the eponymous protagonist appears more distressed, with the narrator’s voice often lingering over his suffering. The purpose of this article is first to present the moments in which the young hero has a physical confrontation with his enemies and, in a second step, to investigate the possible motivations that led the anonymous author to amplify the details relating to the sphere of pain. The comparison with some works which define the standard of courtly romance shows that the emphasis on the protagonist’s misfortunes was intended to bring the text closer to the Arthurian canon and to humanise the figure of Ferguut.
Keywords: Ferguut; Middle Dutch; Fergus; Arthurian romance; courtly literature; rewriting; young hero